Anti-biofim and antibacterial effect of essential oils and their major compounds - Millezi, Alessandra Farias (2016)
Essential oils are plant secondary metabolites commonly used in traditional medicine to treat infectious diseases. Along with their compounds, oils can contribute to development of new antimicrobial/antibiofilm products. Our study evaluated antibacterial activity of essential oils and their major compounds on Escherichia coli and Staphylococcus aureus planktonic cells and anti-biofilm activity. The effect of essential oils and their major compounds on biofilm and planktonic cells was assessed by quantifying the number of viable cells (CFU). Biomass quantification (absorbance=OD570nm) was also performed to evaluate anti-biofilm activity. Planktonic cells were more susceptible to the action of agents. Escherichia coli was reduced by 100% with cinnamon and palmarosa oil. The treatment showed an interesting anti-biofilm activity, whereas green tea essential oil and its major compound, terpinen-4-ol, yielded less effective results. Reduction of viable cells in biofilm biomass was significant. Although our research is one of the first experiments in anti-biofilm activity of essential oils and their compounds against Escherichia coli and Staphylococcus aureus, pharmacological data confirm that the materials used in the trial do not pose health risk. Thus, essential oils and their compounds can be safely used in research to identify new antibacterial and anti-biofilm products against pathogenic bacteria.